2020
DOI: 10.21608/ejbo.2020.26415.1475
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc Oxide Nanoparticles in Ameliorating Salt Tolerance in Soybean

Abstract: A S LONG as we know, little attention has been given to evaluating roles of ZnO nanoparticles (ZnONPs) in plants grown under salinity stress. In the present study, biochemical and molecular responses of salt-stressed soybean cv. Giza111 under different ZnONPs were assessed. Treatment with a high NaCl concentration (250mM) alone caused a significant reduction (65%) in germination percentage as well as a significant decrease in all measured growth parameters (root length, shoot height, fresh and dry weight of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The decline was highest in the non-primed seeds compared with primed ones, thus the seed priming with ZnO NPs could improve the Zn uptake from 8 to 25% depending on the level of salinity imposed. These results agree with those obtained by Gaafar et al (2020) [13], they found that Zn +2 content in soybeans was significantly decreased under salinity stress by 76% compared to control, and presoaking of soybean seeds with ZnO NPs (50 mg L −1 ) increased Zn +2 content even under salinity stress 2.7-fold compared to salt treatment alone.…”
Section: Resultssupporting
confidence: 92%
“…The decline was highest in the non-primed seeds compared with primed ones, thus the seed priming with ZnO NPs could improve the Zn uptake from 8 to 25% depending on the level of salinity imposed. These results agree with those obtained by Gaafar et al (2020) [13], they found that Zn +2 content in soybeans was significantly decreased under salinity stress by 76% compared to control, and presoaking of soybean seeds with ZnO NPs (50 mg L −1 ) increased Zn +2 content even under salinity stress 2.7-fold compared to salt treatment alone.…”
Section: Resultssupporting
confidence: 92%
“…A variety of nanomaterials (NMs) have been reported to enhance plant salt tolerance for growth under saline condition (Almutairi, 2016;Zulfiqar and Ashraf, 2021). For instance, some metal-based nanoparticles, cerium oxide nanoparticles, silica nanoparticles, titanium dioxide nanoparticles, and zinc oxide nanoparticles, can improve salt resistance in multiple plant species (Newkirk et al, 2018;Gaafar et al, 2020;Liu et al, 2021). NMs enhance plant salt tolerance mainly by improving plant photosynthesis performance, promoting ROS detoxification, and maintaining ionic homeostasis and resoring osmotic balance (Newkirk et al, 2018;Liu et al, 2021).…”
Section: Nanobiotechnology and Plant Salt Tolerancementioning
confidence: 99%
“…Also, controlling the process of opening and closing of the stomata to prevent the depletion and consumption of a large amount of water during the photosynthesis process besides, preserve it for only vital processes such as germination, growth, leaf and fruiting formation, and high yield production under these critical physiological conditions. Further, the production and excretion of a large level of proline and glycine betaine contents under salt-stress conditions compared to the control experiment in the aforementioned promising wheat genotypes has added a physiological reason to bear not only to the salt stress but also for all environmental stresses that harm plants and destroy the final output (Abdel Sattar & El-Mouhamady, 2012;El-Mouhamady et al, 2016;Sahoo et al, 2018;Selem, 2019;Shaimaa et al, 2019;Yassin et al, 2019;Ebeed et al, 2019;Loutfy et al, 2019;Genc et al, 2019;El-Mouhamady et al, 2019;Abou Alhamd & Loutfy, 2020;Bacu et al, 2020;Al-Ashkar et al, 2020;Gaafar et al, 2020;El-Mouhamady & Ibrahim, 2020). Results shown in Table 5 are related to heterosis over better-parent asserted the fruitful role of dominance and dominance X dominance gene action.…”
Section: Discussionmentioning
confidence: 99%